2009
DOI: 10.1097/ccm.0b013e31819c3a10
|View full text |Cite
|
Sign up to set email alerts
|

Procedure-related pulmonary hypertension in patients with hepatocellular carcinoma undergoing percutaneous ethanol injection—Role of ethanol, hemolysis, asymmetric dimethylarginine, and the nitric oxide system

Abstract: Procedure-related pulmonary hypertension in patients undergoing PEI is multifactorial. Plasma concentrations of the NO precursor l-arginine are reduced by arginase released from lysed erythrocytes, a condition further exacerbated by the increased concentrations of symmetric dimethylarginine, which may compete with the cellular uptake of l-arginine. The result would be reduced synthesis of NO, the concentration of which would be further decreased extracellularly through free hemoglobin. Predictably, the result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In line with that, Zoccali et al (35) found that after resolution of an acute inflammatory state secondary to infectious processes, L-arginine increased significantly by ϳ15%. Part of this can also be explained by the liberation of arginase, as has been described for other invasive procedures (17).…”
Section: Discussionmentioning
confidence: 95%
“…In line with that, Zoccali et al (35) found that after resolution of an acute inflammatory state secondary to infectious processes, L-arginine increased significantly by ϳ15%. Part of this can also be explained by the liberation of arginase, as has been described for other invasive procedures (17).…”
Section: Discussionmentioning
confidence: 95%
“…However, it also is possible that redistribution during and after HD, 22 ADMA increase by hemolysis, 23 and the effect of acute inflammation on ADMA levels 24 might influence the acute effect of dialysis on ADMA levels.…”
Section: Origin and Removal Of Adma And Sdmamentioning
confidence: 98%
“…Physiologically, increased viscosity induces vasodilation via NO release from endothelial cells 23 . However, in clinical settings associated with endothelial dysfunction, or acute hemolysis, the release of NO due to shear stress is reduced and increased viscosity may lead to increased resistance, as in sickle cell anemia which may lead to a painful vaso‐occlusive crisis 23,31,32 . Reduction of plasma viscosity associated with improved microcirculation was first observed in the treatment of familial hypercholesterolemia 33 .…”
Section: Plasma Viscosity and Its Clinical Applicationsmentioning
confidence: 99%